2022
DOI: 10.3390/jcm11051416
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10/IP10 as a Biomarker Linking Multisystem Inflammatory Syndrome and Left Ventricular Dysfunction in Children with SARS-CoV-2

Abstract: Background: To investigate the diagnostic accuracy of CXCL10/IP10 for left ventricular (LV) dysfunction in multisystemic inflammatory syndrome (MIS-C). Methods: This cross-sectional, longitudinal study included 36 patients with MIS-C. Patients were classified as follows: (1) patients presenting with Kawasaki-like features (group I = 11); (2) patients presenting with LV systolic dysfunction (group II = 9); and (3) other presentations (group III = 3). CXCL10/IP10 levels were measured upon admission and on days 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…IP-10 has been suggested as a potential biomarker to predict left ventricular dysfunction in MIS-C patients. 20 Our MIS-A patients, all with cardiovascular manifestations, demonstrated elevated IP-10 levels. Patient 3's echocardiogram was performed 2 weeks after admission and administration of corticosteroids and IVIG, and it is possible that his cardiac function had improved by the time his cardiac imaging was performed.…”
Section: Discussionmentioning
confidence: 64%
“…IP-10 has been suggested as a potential biomarker to predict left ventricular dysfunction in MIS-C patients. 20 Our MIS-A patients, all with cardiovascular manifestations, demonstrated elevated IP-10 levels. Patient 3's echocardiogram was performed 2 weeks after admission and administration of corticosteroids and IVIG, and it is possible that his cardiac function had improved by the time his cardiac imaging was performed.…”
Section: Discussionmentioning
confidence: 64%
“…Also, it’s reported that the deletion of TNFSF14 may correlate with a decrease in IFN-γ-producing CD4 + T cells, which mediated immunopathogenesis of ocular Herpes simplex virus 1 (HSV-1) infection as the Herpesvirus entry mediator (HVEM) binding partner [ 27 ]. Besides, CXCL10 and CXCL11 bonded the receptor CXCR3 and exerted a potent chemotactic effect on activated T lymphocytes [ 28 30 ]. Additionally, CH25H was induced in response to ZIKV infection, and its enzymatic product 25HC was a critical mediator of host protection against ZIKV, which had also been characterized as a broad-spectrum antiviral drug that inhibited viruses including ZIKV [ 31 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…But also, transforming, and vascular endothelial cellular growth factors (TGF-β/VEGF)) along-side specific matrix metalloproteinases (MMP2, MMP3, MMP9) that represent tissue re-modelling proteins with specific chemotactic factors required to direct leukocyte chemotaxis between GC and throughout the body that include CXCL10 (IP-10), CCL2 (MCP-1), CCL3 (MIP1-α, and CCL11 [51][52][53][54][55]. However, in Middle East Respiratory Syndrome (MERS) IL-1β, IL-8, and IL-6 were highlighted whereas in SARS-CoV-2 CXCL10 does appear to be a key pleiotropic chemokine that has since been clarified in SARS-CoV-2 utilizing CXCR3 expressed on Mϕ, T cells, dendritic cells and both NK and B cells [56][57][58].…”
Section: Coagulopathy and Cytokinesmentioning
confidence: 99%